4*y+8*y+6+2*y=

Simple and best practice solution for 4*y+8*y+6+2*y= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4*y+8*y+6+2*y= equation:


Simplifying
4y + 8y + 6 + 2y = 0

Reorder the terms:
6 + 4y + 8y + 2y = 0

Combine like terms: 4y + 8y = 12y
6 + 12y + 2y = 0

Combine like terms: 12y + 2y = 14y
6 + 14y = 0

Solving
6 + 14y = 0

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-6' to each side of the equation.
6 + -6 + 14y = 0 + -6

Combine like terms: 6 + -6 = 0
0 + 14y = 0 + -6
14y = 0 + -6

Combine like terms: 0 + -6 = -6
14y = -6

Divide each side by '14'.
y = -0.4285714286

Simplifying
y = -0.4285714286

See similar equations:

| =3x(2x-4) | | -8-x=12+x/5 | | 7(2x-3)+4(x+8)= | | 2x+-y=-6 | | 5x=1.2 | | x=3sinx | | y-8+3(y+4)= | | 4-(2x-3)=3+8x-11 | | 144-g=78 | | -10x+2y=14 | | -7=-5y | | 9.5=6-n | | 2x+2(2x-7)=43.6 | | (2x-5)+(4x+7)= | | 3(4+3x)=9 | | 13-2(7+8x)=79 | | 4n-40=7-3n+2 | | 675c-69c+875=9 | | 3n+3=6 | | x^2+3(y+3)=46 | | 16(q-3)+2q-1=5(q-1)+13q+2 | | 4x+7-6x=16-16x+14x-9 | | 3x=0-1 | | 6n-4=14 | | 3x^2-6ax=0 | | 5+(.4)(-.5)(.2)= | | 3w=8.7 | | 3x+12+7x=4 | | 4x^3-30x^2+56x= | | -4.9x^2+19.6x=-24.5 | | 9-8(6+5g)= | | 3.1/2.8= |

Equations solver categories